Galax, omul papusa . Galax, the Puppet-Man - Popescu-Gopo, Ion (Casa de Film 5, 1983)
Fantasy movie about the age of computers in communist Romania. A group of young scientists design a robot, Galax, with several human features. Galax suffers from an existential crisis, struggling between its human and mechanical sides. Galax manages to overcome his condition by programming himself, by adding information to what he was initially given by his creators. He also falls in love with Mariana, a first-year student at the research institute and ultimately attempts to kill himself. The problems created by Galax make the administration board of the institute question the very validity of the project, forcing Galax to run away in order to avoid being terminated.